Identifikasi Hubungan Kekerasan dengan Depresi Lansia Wanita Post Pandemi COVID-19 di Purwobinangun, Sleman - Sumarni DW; Dewi, Wulan May Kusuma; Rahmadani, Alfina Nur (Pusat Studi Wanita dan Keluarga UGM, 2024)
The mental health of elderly women affected by the COVID-19 pandemic is important to consider and is aligned with the development goals of the SDGs. Delayed treatment will exacerbate mental health status, physical health, and the risk of suicide. This is combined with a decrease in socio-economic conditions that can trigger interpersonal tensions and lead to violence in elderly women. Various studies have shown an increase in violence against elderly women during the COVID-19 pandemic. The violence can lead to depression. This study aims to identify the relationship between violence and depression of elderly women post-pandemic COVID-19 in Purwobinangun, Sleman. The method used was cross-sectional study with a sample of 70 elderly women in Purwobinangun who did not have dementia and severe heart disease. Linear regression test was used by using SPSS 25.0 version. The results showed that the prevalence of depression in elderly women was 55.8%, accompanied by elderly women who experienced various types of violence in their daily lives. In addition, there is a significant relationship between violence and depression (p=0.000; t=9.316). Thus it can be concluded that, the more violence experienced, it can increase the condition of depression in elderly women in Purwobinangun, Sleman. Hence, relevant stakeholders should pay attention to the condition of depression and violence in elderly women as well as researchers should conduct new research using qualitative methods.